Diagnóstico de posibles causas de fallecimientos determinadas a través de las necropsias médico legales en el anfiteatro de el Área de la Salud Humana de la Universidad Nacional de Loja - Merino Cueva, Víctor Hugo (2014)
"DIAGNOSIS OF POSSIBLE CAUSES OF DEATH THROUGH CERTAIN LEGAL MEDICAL ANFITEATRO NECROPSY IN AREA OF HUMAN HEALTH NATIONAL UNIVERSITY OF Loja” .It is a work of cross - descriptive prospective which aims to identify the main causes of death in the city of Loja determined through medico-legal necropsies addition to the relationship with age , gender of the deceased 76 reports of medico-legal necropsies performed in the months of April September 2014 information was taken from the files that lie in the Attorney General's Office were analyzed. Once tabulated each of the variables was found that the results coincide with results of similar studies , thus being the head trauma, mechanical asphyxia and drowning occupy the top three main causes of death ; also the male gender is the highest number of deceased and violent death from legally medically ranks first .